Stakeholder Perceptions on the Effects of Extra Tuition on Academic Performance in Public Secondary Schools in Machakos County, Kenya - Mutua, Elizabeth Katile; Maithya, Redempta; Muola, James Matee (International Journal of Education and Research, 2015)
The study sought to establish stakeholder perceptions on effects of extra tuition on academic performance in secondary schools, Machakos County. The sample included 10 principals, 40 teachers and 40 parents Study findings are that extra tuition is widely practiced with 85% of the teachers and 80% of the principals supporting extra tuition. Reasons advanced for extra tuition were that it helps in early coverage of syllabus, boosts performance of individual students and helps identify needs of individual learners among others. Observed t value indicated that perception scores of teachers and principals were t (48) = -0.593, p=0.556 while perception scores of teachers and parents were t (78) = -0.848, p=0.556 meaning that statistically, there was no significant difference between the perception scores of teachers, principals and parents concerning extra tuition on academic performance. This means that their perceptions on the importance of extra tuition were more or less the same. Among the key conclusions were that there is need for the government to employ more teachers and to harmonize extra tuition in schools.
Keywords: Stakeholder percept; Extra tuition; Secondary schools; Academic performance